Which surgery for ground glass opacity lung nodules? - Sara Ricciardi; Federico Davini; Greta Alì; Annalisa De Liperi; Agnese Nesti; Carmelina C. Zirafa; Gaetano Roman; Gabriella Fontanini; Franca M. A. Melfi (临床与病理杂志, 2021)
Objective: Pulmonary ground glass opacity (GGO) nodules represent a significant dilemma in oncology since its diagnosis in clinical practice has increased because of growing application of low dose computed tomography and screening program. The aim of this study is to analyze the clinical and pathological features, the overall survival (OS) and disease-free interval (DFI) in surgically resected solitary ground glass nodules in order to assess the surgical treatment of choice. Methods: We retrospectively analyzed 49 patients (M/F=25/24) with a mean age of 67.7 (range, 40–81) years who underwent lung resection for solitary GGO nodules among 570 reviewed CT of patients who were treated for lung neoplasms between 2010 and 2016. The cohort included 22 pure GGO nodules and 27 part solid GGOs (also called mixed GGOs). Results: Median maximum diameter of GGOs, defined as the largest axial diameter of the lesion on the lung-window setting, was 17 (range, 5–30) mm. GGO nodules were removed by wedge resection, segmentectomy, or lobectomy in 17 (35%), 9 (18%), and 23 (47%) cases, respectively. Pathologic diagnosis was atypical adenomatous hyperplasia (AAH), adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA), invasive adenocarcinoma (IA) or multifocal adenocarcinoma (MAC) in 4 (8.2%), 9 (18.4%), 11 (22.4%), 22 (44.9%) and 3 (6.1%) cases, respectively. With a median follow up of 47 months the OS and DFI of the entire cohort was 46.3 and 43 months, respectively. The histotype (P=0.008), the dimension of GGO (P=0.014) and the PET-SUV max (P=0.001) were independent prognostic factors of worse survival. Sex, age, previous lung surgery, type of surgical resection and the mediastinal lymph-node evaluation did not impact on OS and DFI. Analyzing the 22 pure GGO nodules, we found a 3-year OS and DFI of 98% and 100% respectively, significantly different from 80% and 75% respectively of part-solid GGOs (log-rank P=0.043 and P=0.011). Conclusion: Our data suggest an indolent behaviour of tumour presenting as solitary GGO nodules, especially in case of pure GGOs. In our series wedge resections guarantee the same results in terms of OS and DFI when compared to lobectomies. Sublobar resections without mediastinal lymph-nodes evaluation represent the treatment of choice for pure-GGO. More studies are needed to assess its role for part-solid GGO nodules.